Physician-patient relationship perceived by outpatients at a hospital in Lima, Peru - Mendoza, Cinthya (2016)
Objective: To describe the Physician-patient relationship and to determine the factors associated with a good perception of it by the patients that attend ambulatory care in the Carlos Lanfranco La Hoz Hospital (CLLHH) of the Health Ministry (MINSA), during May 2014. Material and Methods: Transversal-comparative study performed with patients that attend ambulatory care of medical specialties. In this study, a structured semi closed questionnaire called PREMEPA was used and statistical calculations were made with 95% confidence level. Results: A total of 179 patients completed the questionnaire. Of those, 64.8% (116) were women, the average age was 42,1 ± 11,9 years old. 23% (41) of the patients perceived a good physician-patient relationship, 52% (93) regular and 25% (45) a bad relationship. The variables finally associated with a good physician -patient relationship were having between 18-35 years old (OR = 8,1 [IC95%; 1,6-40,1), personally choosing their physicians (OR = 20,5 [IC95%; 5,1-82,5), and be attended by a female physician (OR = 3,1 [IC 95%; 1,01-9,3]). Conclusions: There is a low percentage (23%) of patients that perceive a good physician -patient relationship. Choosing their physician, being a young patient and be attended by a female physician influenced in having a good physician-patient relationship.